Triple VY Advancement Flap For Vulva And Anal Reconstruction In Extensive Perineal Squamous Cell Carcinoma In-Situ - Saphira, Chairani Fitri; Tan, Bien Keem; Tay, Sun Kuie (Jurnal Plastik Rekonstruksi, 2017)
Background : Algorithm for vulvar reconstructions in defects after oncologic resection of vulvar tumors has been established. It goals are to restores form and function for the purpose of coitus, micturition, and defecation. The purpose of this article is to present our experience in vulvar and anal reconstruction. Method : A 43-year-old female with extensive vulvar, perineal and anal squamous cell carcinoma in-situ and groin lymph nodes metastasis requiring defect coverage after tumor resection. The defects involving exposed soft tissue around vulvar, perineal and anal areas. Result : Vulvar and anal reconstruction was done in stages utilizing triple VY advancement flap. The reconstruction was successful with preservation of sexual and anal functions; and minimal scarring. Conclution: Extensive vulvar and anal defects can be reconstructed by recruiting local tissue. VY advancement flap is one of the best options in these reconstructions.